2013
DOI: 10.3390/molecules18033595
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Celecoxib Derivatives as Possible Anti-Inflammatory, Analgesic, Antioxidant, Anticancer and Anti-HCV Agents

Abstract: A series of novel N-(3-substituted aryl/alkyl-4-oxo-1,3-thiazolidin-2-ylidene)-4-[5-(4-methylphenyl)-3-(trifluoromethyl)-1H-pyrazol-1-yl]benzenesulfonamides 2a-e were synthesized by the addition of ethyl -bromoacetate and anhydrous sodium acetate in dry ethanol to N-(substituted aryl/alkylcarbamothioyl)-4-[5-(4-methylphenyl)-3-(trifluoromethyl)-1H-pyrazol-1-yl]benzene sulfonamides 1a-e, which were synthesized by the reaction of alkyl/aryl isothiocyanates with celecoxib. The structures of the isolated OPEN ACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 36 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…The sulfonamide linkage plays a vital role as a key constituent in a number of biologically active molecules. Up to now, sulfonamides have been known to exhibit a wide variety of biological activities, such as antibacterial (Subhakara Reddy et al, 2012; Himel et al, 1971), antifungal (Hanafy et al, 2007), anti-inflammatory ISSN 2053ISSN -2296 # 2017 International Union of Crystallography (Kuçukguzel et al, 2013), antitumor , anticancer (Mansour et al, 2011), anti-HIV (Sahu et al, 2007) and antitubercular activities (Vora & Mehta, 2012). In recent years, extensive research has been carried out on the synthesis and evaluation of the pharmacological activities of molecules containing the sulfonamide moiety for different activities, and have been reported to be important pharmacophores (Mohan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfonamide linkage plays a vital role as a key constituent in a number of biologically active molecules. Up to now, sulfonamides have been known to exhibit a wide variety of biological activities, such as antibacterial (Subhakara Reddy et al, 2012; Himel et al, 1971), antifungal (Hanafy et al, 2007), anti-inflammatory ISSN 2053ISSN -2296 # 2017 International Union of Crystallography (Kuçukguzel et al, 2013), antitumor , anticancer (Mansour et al, 2011), anti-HIV (Sahu et al, 2007) and antitubercular activities (Vora & Mehta, 2012). In recent years, extensive research has been carried out on the synthesis and evaluation of the pharmacological activities of molecules containing the sulfonamide moiety for different activities, and have been reported to be important pharmacophores (Mohan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR and 13 C NMR spectra in DMSO-d 6 were recorded on a BRUKER AVANCE-DPX (Billerica, MA) spectrometer (400 MHz) and chemical shifts are given in ppm downfield from tetramethylsilane (TMS) as an internal standard using DMSO-d 6 as solvent. Data are reported as follows: chemical shift, multiplicity (br.…”
Section: Generalmentioning
confidence: 99%
“…This drug was a much weaker one (KI of 2520 nM) inhibitor against CA II 4 . It has been declared that sulfonylthiourea and 4-thiazolidinone structures exhibit antitumoral activity 5,6 . It has been also indicated that some 4-thiazolidinone derivatives selectively inhibit COX-2 enzyme, an important target for some anticancer studies 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 upregulation has also been correlated with the presence of inflammatory cells in hepatocarcinogenesis and tumor angiogenesis in HCC 4 . COX-2 inhibitors have displayed significant antiproliferative effects in many human HCC cell lines 5 . Further, investigations on animal models of liver cancer have shown that NSAIDs, including selective COX-2 inhibitors, exhibit chemopreventive as well as therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%